Telehealth Cognitive Behavior Therapy for Co‐Occurring Insomnia and Depression Symptoms in Older Adults. Issue 10 (22nd August 2013) - Lichstein, Kenneth L.; Scogin, Forrest; Thomas, S. Justin; DiNapoli, Elizabeth A.; Dillon, Haley R.; McFadden, Anna
<x xml:space="preserve">Abstract</x> Objective Telehealth has proven effective with a wide range of disorders, but there is a paucity of data on the use of telehealth using cognitive‐behavior therapy (CBT) with late‐life insomnia and depression. This pilot study was designed to examine the feasibility and effectiveness of using telehealth to treat older adults with comorbid insomnia and depression living in rural Alabama. Method Five patients received 10 sessions of CBT for insomnia and depression. Patients were engaged in treatment via Skype from their primary care physician's office. Assessments were conducted at baseline, posttreatment, and 2‐month follow‐up. Results Patients exhibited clinically significant improvement in both insomnia (sleep diaries and Insomnia Severity Index) and depression (Hamilton Rating Scale for Depression) at posttreatment, and these gains were well maintained at 2‐month follow‐up. Conclusions These preliminary data suggest that telehealth may be an effective means of providing treatment to older adults, including underserved populations.